Nanostructured Materials: Less is More - Rajan, Jose (Penerbit Universiti Malaysia Pahang, 2016)
Rise in the global population with improved living standard need more consumables than the past. The human population has grown from 6 billion in 1999 to 7 billion in 2012, i.e., one billion is added in 12 years of time, and is expected to reach 10 billion by 2050 – 2060. However, the planet Earth marks a depletion of its natural resources leading to a situation of sharing limited resources for a larger population; which would require strategic solutions. Nanoscience and technology has been emerged as a promising solution based on many properties of nanomaterials – they provide us a way to do things in a better way using lesser amounts of materials. Nanostructured materials are defined by ASTM as “materials containing features between approximately 1 and 100 nm and to differentiate those properties different from properties found in either molecules or the bulk (interior) of larger, micron-sized system”. Many of the natural systems are built using nanostructured materials; development of functional surface upon nanostructuring and controlling their optical and electronic properties has long been researched and a clear understanding is reached on this topic. Surface of nanostructured materials not only offer beneficial effects but, equally importantly, undesirable effects also. Therefore, intention of most research on nanostructured materials has been to use the beneficial effects bypassing the detrimental ones. Alternatively, modification of nanostructured materials’ surface by tuning their morphologies has been an intense topic. This lecture will be organized on explaining the properties of the nanostructured materials and how the properties of the nanomaterials add performance in a nanostructured devices, with emphasis on energy devices.